Care and repair of advanced composites - Armstrong, Keith B.; Chesmar, Eric; Museux, Francois; Cole, William F. (SAE International, 2020)
The new edition of the well known Care and repair of advanced composites, 3rd edition, improves on the usefulness of this practical guide geared towards the aerospace industry. A fully updated approach to the training syllabus recommended for repair design engineers and composite repair mechanics. Metal bonding has been included partly because the defi nition of "composite" can be interpreted to include metal-skinned honeycomb panels, and partly because some composite parts have metal fittings or reinforcements that must be treated before bonding. This third edition also covers a number of the problems experienced in service, some of which may be applicable to metallic sandwich panels, offers suggestions for design improvements, including repair design as a particular topic, and regulatory changes.